2021
DOI: 10.1186/s12906-021-03451-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel mesoporous silica nanocarriers containing gold; a rapid diagnostic tool for tuberculosis

Abstract: Tuberculosis (TB) is major health concern and reason of deaths from decades to current date. Even though with a lot of advancements, diagnostic techniques, and discovery of standard antibiotics TB remains crucial challenge and can create worst scenario for human health in near future. Nanoparticles play emerging role in diagnosis and treatment of TB. In this study, we developed mesoporous silica nanoparticles containing gold (MSNs@GNPs) for rapid diagnosis and treatment of TB. The physicochemical characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The fabricated composite showed a dual effect for the rapid diagnosis and treatment of TB, so it is highly recommended for use in clinical in vivo studies. 5 A similar study has recently confirmed the high tendency of silica mesoporous NPs towards high loading efficiency to be one of the best options for drug loading resistance purposes. Ag NPs have proven to have great bactericidal activity.…”
Section: Materials Advances Reviewmentioning
confidence: 70%
See 1 more Smart Citation
“…The fabricated composite showed a dual effect for the rapid diagnosis and treatment of TB, so it is highly recommended for use in clinical in vivo studies. 5 A similar study has recently confirmed the high tendency of silica mesoporous NPs towards high loading efficiency to be one of the best options for drug loading resistance purposes. Ag NPs have proven to have great bactericidal activity.…”
Section: Materials Advances Reviewmentioning
confidence: 70%
“…4 TB negatively affects the lungs (i.e., pulmonary TB) and the central nervous system (CNS), causing severe meningitis. 5 TB is primarily caused by Mycobacterium tuberculosis, which is a type of bacteria that can be identified as either Grampositive or Gram-negative on a gram stain. 6 Several clinical approaches have reported the diagnosis of TB, encompassing culture of the tracheal aspirate, cerebrospinal fluid (CSF), gastric washings, chest X-ray, and skin examination.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial properties were studied using MIC and minimum bactericidal concentration methods [218]. Mesoporous silica nanoparticles (MSNs) containing gold nanoparticles (MSNs@GNP) can inhibit M. tuberculosis growth and produce a synergistic effect against M. tuberculosis, making it safe for TB treatment [219]. Another important application of GNP is in TB diagnosis.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%